Synchronous presentation of acute cholecystitis and acute appendicitis successful treatment in one step laparoscopic procedure. A case series and literature review. (September 2021) - Nahidi, Seyed Mohammad; Khan, Khuram; Engler, Christopher; Tickoo, Sharang; Biggs, Carina
Abstract: Introduction: Hundreds of thousands of cholecystectomies and appendectomies are performed in the United States annually. Due to the prevalence of cholecystitis and appendicitis, a subset of patients will require both operations. The limited literature describing these patients supports a laparoscopic approach over open surgery; consistent with the advantages of laparotomy over open surgery in the treatment of each condition individually. Case presentation: We report two cases where a patient presented with cholecystitis and appendicitis simultaneously. An abdominal computer tomography (CT) scan revealed the presence of the two diagnoses, which was then confirmed by an abdominal ultrasound. A four-access port was utilized for simultaneous appendectomy and cholecystectomy. Discussion: A review of the literature indicates that simultaneous infection with appendicitis and cholecystitis is rare, and thus clinical presentation, lab work, and imaging studies are all needed to support such a diagnosis. Potential findings on imaging in these patients may include distended gallbladder with thickened wall and fluid-filled dilated appendix with mural enhancement. In the event that both clinical presentation and further work-up indicate both pathologies, laparoscopic intervention is suitable. A four-access port is deemed the conservative approach to dealing with such cases. Conclusion: Finding a single diagnosis responsible for a patient's illness is a high priority in an acute care setting, a concept known as diagnostic parsimony. However, it is inevitable that very common illnesses will be comorbid in a subset of patients, and physicians should be prepared to consider contemporaneous illness in the isolated circumstances it is warranted. Highlights: Simultaneous appendicitis and cholecystitis is rare. Computer tomography is an accurate diagnostic tool in cases such as this. A four-access port is deemed the conservative approach to dealing with such cases.